Biosafety Regulation : A Review of International Approaches - World Bank (Washington, DC, 2013)
The focus of this report is crop biotechnology, as developing countries are faced with evaluating genetically engineered plants for human, livestock, and environmental safety. These genetically engineered plants can potentially contribute to agricultural productivity in developing regions when appropriately deployed, but there is uncertainty about the potential for adverse consequences to environmental and human health. The result has been regulatory regimes that are applied specifically to assess the safety of these products. The experiences of countries with long-established biosafety systems, while not providing a single best practice model for ensuring biosafety, point to a common set of issues facing governments and policymakers. These issues are in the areas of: the design and objectives of a regulatory system; implementation mechanisms and regulatory structures; a series of crosscutting considerations including transparency, public involvement, integrating biosafety regulation in other national policy objectives; and regional or international harmonization. Drawing from selected country experiences, the report explores each of these issues in detail and provides policy direction on points of consensus. Additional country-specific detail on the regulatory approaches tested in countries where genetically engineered plants have been approved for commercialization is presented.